1993
DOI: 10.1099/0022-1317-74-2-293
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of Sindbis virus proteins in mosquito cells as determined by immunofluorescence and immunoelectron microscopy

Abstract: Two Aedes albopietus (mosquito) subclones, C7-10 and C6/36, were examined by immunofluorescence and immunoelectron microscopy for the distribution of Sindbis virus structural and non-structural proteins. Both the viral glycoproteins, E1 and E2, and the non-structural proteins, nsP1 and nsP2, were found within vesicles and electron-dense, amorphous matrices associated with Sindbis virus infection. The labelling patterns indicated that both replication of viral RNA and production of virus particles were localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Cells infected with either poliovirus or Sindbis contain de novo synthesized vesicular structures containing polypeptides which are components of the viral RNA biosynthetic machinery (Bienz et al, 1992;Miller and Brown, 1993). For poliovirus it is clear that these structures are sites of RNA replication (Takeda et al, 1986;Bienz et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Cells infected with either poliovirus or Sindbis contain de novo synthesized vesicular structures containing polypeptides which are components of the viral RNA biosynthetic machinery (Bienz et al, 1992;Miller and Brown, 1993). For poliovirus it is clear that these structures are sites of RNA replication (Takeda et al, 1986;Bienz et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, plasmid DNA was linearized by digestion with NotI, and equal amounts of DNA were used as a template to synthesize RNA transcripts, using a T7 mMessage mMachine in vitro transcription kit (Ambion) according to the manufacturer's directions. A portion of each transcription reaction was radiolabeled using 35 S-UTP (GE Healthcare). To measure 35 S-UTP incorporation, labeled transcripts were bound to glass filters, washed, and quantified using a scintillation counter.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of this, approximately one-half of nsP2 is found in the nucleus of infected mammalian cells, and nsP2 is the only alphavirus nonstructural protein present in the nucleus (1,20,35,42,50,51). Studies performed with SFV, an Old World alphavirus, identified PRRRV as the nuclear localization signal (NLS) in nsP2 and defined the central arginine residue in the sequence as essential for nsP2 nuclear localization.…”
mentioning
confidence: 99%
“…nsP2 also possesses poorly understood auxiliary functions that may affect the outcome of infection. Although the replication cycle occurs in the cytoplasm, nsP2 is the only alphavirus nonstructural protein that is present in both the cytoplasm and the nucleus of infected mammalian cells (3,34,45; S. A. Montgomery and R. E. Johnston, unpublished data). Although the role of nuclear nsP2 remains elusive, disruption of nsP2 nuclear localization compromises the ability of the virus to spread in the brain (11).…”
mentioning
confidence: 99%
“…For electroporation, BHK-21 cells were cultured overnight in medium containing 10% fetal bovine serum (FBS), harvested when subconfluent, and prepared for electroporation as previously described (8,29). HEK-293 cells (ATCC, passage [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] were incubated at 37°C under 5% CO 2 and maintained in Dulbecco modified Eagle medium (Gibco) supplemented with 10% FBS, 100 U of penicillin per ml, and 0.5 mg of streptomycin per ml.…”
mentioning
confidence: 99%